Neutrophils in COVID-19: Not Innocent Bystanders - McKenna, Ellen; Wubben, Richard; Isaza-Correa, Johana M.; Melo, Ashanty M.; Mhaonaigh, Aisling Ui; Conlon, Niall; O’Donnell, James S.; Ní Cheallaigh, Clíona; Hurley, Tim; Stevenson, Nigel J.; Little, Mark A.; Molloy, Eleanor J. (Frontiers in Immunology, 2022)
Unusually for a viral infection, the immunological phenotype of severe COVID-19 is characterised by a depleted lymphocyte and elevated neutrophil count, with the neutrophil-to-lymphocyte ratio correlating with disease severity. Neutrophils are the most abundant immune cell in the bloodstream and comprise different subpopulations with pleiotropic actions that are vital for host immunity. Unique neutrophil subpopulations vary in their capacity to mount antimicrobial responses, including NETosis (the generation of neutrophil extracellular traps), degranulation and de novo production of cytokines and chemokines. These processes play a role in antiviral immunity, but may also contribute to the local and systemic tissue damage seen in acute SARS-CoV-2 infection. Neutrophils also contribute to complications of COVID-19 such as thrombosis, acute respiratory distress syndrome and multisystem inflammatory disease in children. In this Progress review, we discuss the anti-viral and pathological roles of neutrophils in SARS-CoV-2 infection, and potential therapeutic strategies for COVID-19 that target neutrophil-mediated inflammatory responses.